2015
DOI: 10.2337/db14-1926
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HSP90 Ameliorates Nephropathy and Atherosclerosis Through Suppression of NF-κB and STAT Signaling Pathways in Diabetic Mice

Abstract: Heat shock proteins (HSPs) are induced by cellular stress and function as molecular chaperones that regulate protein folding. Diabetes impairs the function/expression of many HSPs, including HSP70 and HSP90, key regulators of pathological mechanisms involved in diabetes complications. Therefore, we investigated whether pharmacological HSP90 inhibition ameliorates diabetes-associated renal damage and atheroprogression in a mouse model of combined hyperglycemia and hyperlipidemia (streptozotocin-induced diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 50 publications
6
54
0
Order By: Relevance
“…This finding was consistent with a known mechanism of NF-κB in diabetic renal inflammation918192021222324. Indeed, we have previously reported that human CRP can promote renal inflammation by activating NF-κB signaling via the CD32/64-dependent mechanism in a mouse model of type 1 diabetic nephropathy induced in CRPtg mice and in vitro 9.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was consistent with a known mechanism of NF-κB in diabetic renal inflammation918192021222324. Indeed, we have previously reported that human CRP can promote renal inflammation by activating NF-κB signaling via the CD32/64-dependent mechanism in a mouse model of type 1 diabetic nephropathy induced in CRPtg mice and in vitro 9.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that the DM group had increased protein and mRNA levels of NF-κB p65 and its active form phospho-NF-κB p65. The result was consistent with previous studies, which found increased NF-κB activity in diabetic animals (5,7,30). IκBα is an inhibitor of the activation of NF-κB p65, which can suppress the phosphorylation of NF-κB p65.…”
Section: Discussionsupporting
confidence: 83%
“…The diabetic rats treated with AG showed significantly lower TNF‐α, IL‐6, and IL‐1β serum levels, as well as the effect of high dose group better than positive group. Because the NF‐κB signaling pathway plays a key role in renal inflammation in DN (Lazaro et al, ), we also investigated whether AG affects renal NF‐κB signaling in diabetic rats. As shown in Figure d, compared with the control rats, the diabetic rats showed 2.37‐fold and 2.53‐fold increased expression of renal phospho‐IκBα (p‐IκBα) and p‐NF‐κBp65, respectively, and 0.39‐fold decreased IκBα expression.…”
Section: Resultsmentioning
confidence: 99%